How resources of universities influence industry cooperation - Gyeong Min Nam; Dae Geon Kim; Sang Ok Choi (Journal of Open Innovation: Technology, Market, and Complexity, 2019)
In Korea, cooperation between university and company is mainly encouraged by government policy as the Triple Helix's statist model. Since 2003, the government started a variety of university financial support program, and in 2014, it reached to the point that 31 ministries conducted 408 programs in total. Most projects focused on training human resources and supporting Research and development, which is considered as the core function of universities, but some of the projects are designed to support the industry-academia cooperation. For instance, the Ministry of Education ran 'Leaders in University and Industry Cooperation (LINC)' program. LINC is a follow-up project of Human Resources Development for the Leading Industries, Industry-Academia Cooperation-oriented University, and Focal Point Research program. Accordingly, it aimed to create university-industry cooperative models, and nurture talents based on regional economy's demand. The program provided approximately 230M per year for over 50 universities across the country. It was one of the highly influential grant programs considering the fact that there are about 200 universities nationwide and an annual budget of university is 900 billion on average. In this context, this study is to assess the influence of resources of universities capacity on the achievement of university-industry cooperation and explore whether a government-initiated policy has a significant effect using data from government information disclosure system on education.
Keywords: 650; university-industry cooperation; triple helix; resource-dependent; open innovation; LINC